Thermal decomposition kinetics and dielectric properties of polyurethane grafted onto PEMA-co-PHEMA - Demir, Pinar; Dusukcan, Ilknur Yirtar (Springer, 2018)
Segmented polyurethane (PU) was synthesized via grafting from PEMA-co-PHEMA. This polyurethane was characterized by experimental measurements such as FTIR, H-1 NMR, thermogravimetric analysis (TGA) and DSC techniques. The degradation process reaction mechanism and the kinetic parameters about the polyurethane grafted onto PEMA-co-PHEMA in nitrogen environment were examined by TGA at varied heating rates. The activation energies of thermal degradation for polyurethane by the Kissinger, Flynn-Wall-Ozawa and Tang methods, without knowing the reaction mechanism (RM), were found to be 173.65, 173.85 and 163.38 kJ/mol, respectively. According to dynamic measurements, the analysis of every process mechanism of Coats-Redfern and Van Krevelen methods demonstrated that the most likely model for the decomposition process of polyurethane complies with the three-dimensional diffusion, D3 mechanism. Analysis of the experimental results proposed that the reaction mechanism in the conversion range (2-50%) was a D3 [three-dimensional diffusion (Jander equation)] deceleration type. The dielectric properties of polyurethane were measured at varied frequencies at room temperature. The capacitance measurements were carried out at room temperature over the frequency range 1-10,000 kHz. Conductivity sigma* and the real and imaginary parts of the dielectric permittivity epsilon* were obtained for PEMA-co-PHEMA-g-PCL with soft segment of PU, and PEMA-co-PHEMA-g-PU. The dielectric constant of all samples decreased as the frequency increased.
Keywords: Polyurethane; TGA; Thermal decomposition kinetic; Dielectric properties